2011
DOI: 10.1088/1367-2630/13/5/055015
|View full text |Cite
|
Sign up to set email alerts
|

On the viscosity-to-entropy density ratio for unitary Bose and Fermi gases

Abstract: We calculate the ratio of the viscosity to the entropy density for both Bose and Fermi gases in the unitary limit using a new approach to the quantum statistical mechanics of gases based on the S-matrix. In the unitary limit the scattering length diverges and the S-matrix equals −1. For the fermion case we obtain η/s > 4.7 times the proposed lower bound of /4πk B which came from the AdS/CFT correspondence for gauge theories, consistent with the most recent experiments. For the bosonic case we present evidence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…(8), q,c → 2q,2c, with Eqs. (17) and (18) still valid. In other words, henceforth, q,c will refer to one of the two components.…”
Section: S-matrix-based Formalism For the Thermodynamicsmentioning
confidence: 90%
See 1 more Smart Citation
“…(8), q,c → 2q,2c, with Eqs. (17) and (18) still valid. In other words, henceforth, q,c will refer to one of the two components.…”
Section: S-matrix-based Formalism For the Thermodynamicsmentioning
confidence: 90%
“…For instance, it was applied to the so-called unitary limit in three dimensions where the scattering length diverges and the S matrix becomes simply −1, and reasonable results were obtained for the critical temperature [15,16]. The ratio of the viscosity to entropy density was also calculated using this method [17] and agrees well with the most recent experiments [18]. Thus, although the method cannot really compete with numerical methods such as Monte Carlo, it can be justified as an exploratory tool for regimes that have not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…This correction is imaginary and corresponds to damping. Near T c , employing the notion of "minimal quantum viscosity" [58], one finds δc/c = −iAmn 1 ω/η, where η is the viscosity calculated on the symmetry axis and A ∼ 8.12 × 10 −4 . In the high T classical limit one instead finds A ∼ 1.62 × 10 −3 .…”
Section: First Soundmentioning
confidence: 99%
“…Müller et al [9] studied the ratio g=s of graphene and also found j > j 0 in that case. Two-dimensional Fermi gases also obey the inequality j > j 0 [10,11]. Csernai et al [12] pointed out some similarities between the general behavior of j near the critical points of He, N 2 , and H 2 O and that of the phase transition from hadrons to the quark-gluon plasma.…”
Section: Introductionmentioning
confidence: 99%